Influence of Mineral Admixtures on the Properties of Magnesium Oxychloride Cement Lean Concrete. (14th April 2023) - Guan, Bowen; Di, Wenjin; Wu, Jiayu; Wang, Faping; Zhang, Shuowen; He, Zhenqing
Abstract : This study investigated the effects of light-burned magnesia, fly ash (FA), dolomite powder (DP), and limestone powder (LP) contents on the performance of magnesium oxychloride cement lean concrete (MOCLC). The effects of light-burned magnesia and mineral admixture content on the mechanical properties and durability of MOCLC were tested by the compressive strength test, splitting strength test, water resistance test, shrinkage test, and fatigue test, respectively. The results revealed that the optimum dosage of MgO was 4%. The optimum dosages of FA, DP, and LP were 25%, 20%, and 20% of the cement dosage, respectively. The compressive and splitting strengths of the MOCLC were decreased by the addition of FA and DP. Due to part of the internal pores of MOCLC were filled with FA and DP, the decomposition of the main strength phase 5Mg (OH)2 ·MgCl2 ·8H2 O (phase 5) was suppressed and the water resistance of MOCLC was improved. The addition of FA and DP also improved the shrinkage resistance, and the fatigue resistance of MOCLC was also improved by the addition of FA and DP. The water resistance, shrinkage, and fatigue properties of MOCLC with a FA content of 25% were better than those of MOCLC with DP and LP.